Mineralization of the antineoplastic drug carboplatin by heterogeneous photocatalysis with simultaneous synthesis of platinum-modified TiO2 catalysts. Issue 2 (April 2018) - Kitsiou, Vasiliki; Zachariadis, George A.; Lambropoulou, Dimitra A.; Tsiplakides, Dimitrios; Poulios, Ioannis
Highlights: TiO2 photocatalytic oxidation of platinum anticancer drug carboplatin was studied. Photo-reduction of Pt ions occurred simultaneously with photo-oxidation of the drug. For TiO2 /UV-A, 100% deposition of Pt is achieved within 60 min of photo-oxidation. Synthesized Pt-modified TiO2 P25 was more effective compared to the unmodified one. Abstract: Photocatalytic oxidation of carboplatin, a platinum antineoplastic drug, has been investigated in aqueous heterogeneous solutions containing TiO2 photocatalysts. The current study, besides the photocatalytic degradation of the drug, examines the utilization of the photo-reduction process occurring on the surface of the catalyst, leading simultaneously to the photo-deposition and recovery of platinum. TiO2 photocatalytic process was evaluated for its ability to degrade the molecule of carboplatin and concurrently result in the synthesis of efficient platinum modified TiO2 catalysts. The degradation kinetic was studied under different operational conditions, such as type of photocatalyst, catalyst loading, initial pH and addition of electron acceptors. Three systems were evaluated namely, TiO2 P25 under UV-A and TiO2 Kronos vlp 7000 under UV-A or visible illumination, with respect to their activity for substrate degradation and mineralization and their ability to bind platinum on their surface during photocatalytic oxidation of the drug. The initial degradation rate (r0 ) decreased in the order TiO2 P25/UV-A > TiO2 Kronos vlp 7000/UV-A > TiO2 Kronos vlp 7000/visible light. For TiO2 P25/UV-A, the addition of 100 mg L −1  H2 O2 increases slightly the initial mineralization rate, while degradation rates gradually decrease as photocatalysis takes place in neutral and alkaline pH. Phytotoxicity measurements, showed that heterogeneous photocatalytic oxidation in the presence of TiO2 P25 is capable of reducing the phytotoxicity of carboplatin. For TiO2 P25 and TiO2 Kronos vlp 7000 under UV-A illumination, photo-reduction and deposition of platinum is fully accomplished within 60 min of oxidation, while for TiO2 Kronos vlp 7000 in the presence of visible light, the percentage of platinum deposited on the surface of the catalyst reaches 40%. Platinum photo-deposition is feasible, employing TiO2 P25, even after the catalyst is reused. The synthesized platinum modified TiO2 P25, demonstrated higher photocatalytic efficiency in comparison to the bare one, leading to 100% degradation of the model pollutant malachite green and 40% DOC reduction, after 30 min of photo-oxidation.